Career Development Services (CDS) at the University Level: A Study on Two Private Universities in Bangladesh (Journal of Business and Technology (Dhaka), 2014)
In this paper an attempt has been made to analyze the importance of educating students through various missions of professional development activities of a university. Through its focus on teaching and learning, research and discovery, and outreach and engagement, the university creates, conveys, and applies knowledge to expand personal growth and opportunity, advance social and community development, foster economic competitiveness, and improve quality of life. Bangladesh, as a developing nation, experiences one of the most acute unemployment situations in the world. Getting a suitable job or building right career in the expected way has now-a-days become very difficult. Emphasis has been given on building skilled human resources by undertaking job oriented academic programs, arranging internship, job placement, workshop and facilitating opportunities to study abroad for higher education. Because, without imparting qualitative education and proper counseling a fresh graduate may lose the right way to approach in getting a better livelihood and build healthier career. The university, where the students are taught, can play a pivotal role in guiding them and building their professional skills in the way of achieving the goal. This article will analyze how a university can take part with students professional development activities and prepares its students for job market at home and abroad. DOI: http://dx.doi.org/10.3329/jbt.v8i1-2.18288 Journal of Business and Technology (Dhaka) Vol.8(1-2) 2013; 95-113